Recent Advances in the Valorization of Lignin: A Key Focus on Pretreatment, Characterization, and Catalytic Depolymerization Strategies for Future Biorefineries. (10th December 2021) - Mankar, Akshay R.; Modak, Arindam; Pant, Kamal Kishore
Abstract: Lignin is the largest renewable source of aromatics with an annual production of ≈50 to 70 million tons worldwide. Unfortunately, despite being a rich source of aromatic chemicals, almost 98% to 99% of lignin is burned as a low‐value fuel and only 1% to 2% is utilized as high‐value chemicals. It is noteworthy that lignin is cross‐linked with carbohydrate fractions of lignocellulosic biomass (LCB) through a stable lignin‐carbohydrate covalent complex, making it the main hurdle in converting LCB. Moreover, the stability of the inter‐unit linkages (COC, CC) and the strong interactions among the aromatic units, makes the separation into aromatic monomers challenging. Hence, a delignification pathway through a sustainable approach represents a formidable challenge for the development of future biorefineries. A breakthrough in several technological pathways, e.g., LCB fractionation, lignin characterization/depolymerization, and economic analysis are being considered. However, there remains a dearth of in‐depth understanding and a thorough know‐how. This review navigates readers through the latest cutting‐edge innovations in these four interconnected biorefinery aspects, and may inspire others to propagate the growth of biorefineries in the upcoming years. Overall, the objective of this review is to provide insights into lignin valorization technologies which may guide the future research toward sustainable biorefineries. Abstract : Development of a sustainable lignin‐based future biorefinery is dependent on the pretreatment of lignocellulosic biomass for delignification, followed by valorization of the lignin, its characterization, and catalytic conversion into valuable aromatics, which are discussed in the current review.